Reflex Testing Rules for Cell Count and Differentiation of Nucleated Elements in Pleural and Ascitic Fluids on Sysmex XE-5000. (April 2016) - Buoro, Sabrina; Appassiti Esposito, Sara; Vavassori, Mauro; Mecca, Tommaso; Ottomano, Cosimo; Dominoni, Paola; Seghezzi, Michela; Candiago, Elisabetta; Farina, Claudio; Gianatti, Andrea; Crippa, Alberto; Lippi, Giuseppe
Flow cytometry is widely used in many laboratories for automated nucleated cell counts and their differentiation in body fluids. The implementation of new reflex testing rules on these automated instruments could open new frontiers in laboratory workflow, improving characterization of body fluids and clinical diagnosis and decreasing costs. Ascitic (150) and pleural (33) fluids were collected and assessed by XE-5000 and optical microscopy. Cell counts performed with the methods showed a Pearson's correlation of 0.98 ( p < 0.0001), Passing–Bablok regression y = 0.99 x + 2.44, and bias of 32.3. In ascitic fluids, the best diagnostic performance was found for polymorphonuclear and neutrophil counts on XE-5000, which exhibited areas under the curve (AUCs) 0.98 ( p < 0.0001) and 0.99 ( p < 0.0001), respectively. In pleural fluids the best diagnostic performance was found for polymorphonuclear percent parameter, which displayed 0.97 ( p < 0.0001). Specific reflex test rules based on these parameters were characterized by 92% diagnostic concordance, 1.00 sensitivity, and 0.84 specificity with optical microscopy. The application of a set of reflex testing rules may improve the diagnostic performance of XE-5000, increasing its reliability for routine automated cell count in body fluids. We acknowledge that further studies should be planned to validate our findings according to clinical data.